PEMISAHAN DESA/KELURAHAN DI KABUPATEN SEMARANG MENURUT STATUS DAERAH MENGGUNAKAN ANALISIS DISKRIMINAN KUADRATIK KLASIK DAN DISKRIMINAN KUADRATIK ROBUST - Afianti Sonya Kurniasari; Diah Safitri; Sudarno Sudarno (Jurnal Gaussian, 2014)
Semarang Regency is one of 29 counties and 6 towns in Central Java province. In the district there are rural areas and urban areas. Discriminant analysis is a technique related to the separation of objects into different groups that have been set previously, thus, discriminant analysis can be used to separate village in Semarang Regency into urban or rural groups. Linear discriminant analysis assumes that the covariance matrix of the two groups are equal, If the assumption of equality covariance matrix is denied, function of quadratic discriminant can be used for classification. Classical estimation for the sample mean vector and sample covariance matrix is very sensitive to the presence of outliers in the observations and the functioning of the separation can be non-robust. Estimators that can be used to cope with data containing outliers are the Minimum Covariance Determinant. Robust discriminant analysis is obtained by replacing the mean and covariance matrix using the classic MCD estimator. After analysis is performed, obtained result the data of 2011 Village Potential contains outlier, so that the robust quadratic discriminant analysis more appropriate because it can provide precision the results of separation 89,79% while classical quadratic discriminant analysis give exactness of 87,23%.